2015
DOI: 10.1002/ldr.2383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aggregate Stability Measurement Methods for Clay‐rich Soils in Asartepe Catchment of Turkey

Abstract: There are many methods and approaches of determining the structural status of soils as a quality indicator. But there is no common method for aggregate stability measurement that can be used for all soil types and circumstances affecting aggregate disruption. This study aimed to compare different aggregate stability methods for clay‐rich soil systems of semi‐arid lands, where desertification is a significant threat to land resources. The study area is located in the Asartepe catchment of Ankara, Turkey, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
2
16
0
3
Order By: Relevance
“…Higher WSA was observed in AAO and GL compared to the other types of land use because the lands had not been used for the last 20 years. Our results are in accordance with the available literature [32,34,35], which revealed that the WSA of cropland could be affected by the use of heavy farm machinery, animals, and human activity [1]. The results of the different aggregate size fractions in terms of DSA indicated that the 2-1 mm and 1-0.5 mm fractions were both affected in cropland (Table 4), with the DSA at 0-20 cm increasing in the order of Clm, Clw, CAO, GL, SGL, and AAO.…”
Section: The Dsa and Wsa Distribution Of Soil Aggregate Compositions (%)supporting
confidence: 93%
“…Higher WSA was observed in AAO and GL compared to the other types of land use because the lands had not been used for the last 20 years. Our results are in accordance with the available literature [32,34,35], which revealed that the WSA of cropland could be affected by the use of heavy farm machinery, animals, and human activity [1]. The results of the different aggregate size fractions in terms of DSA indicated that the 2-1 mm and 1-0.5 mm fractions were both affected in cropland (Table 4), with the DSA at 0-20 cm increasing in the order of Clm, Clw, CAO, GL, SGL, and AAO.…”
Section: The Dsa and Wsa Distribution Of Soil Aggregate Compositions (%)supporting
confidence: 93%
“…Our results corroborated with findings of Nath & Lal (), who have reported that higher water stable aggregation and MWD in Rayne silt loam soils (Typic Hapludult). Although our study did not find any effect of tillage, residue management or fertiliser application on WSA, previous studies have found tillage effects (Kumar et al ., ; Saygin et al ., ; Sundermeier et al ., ; Yagüe et al ., ). Sundermeier et al .…”
Section: Discussionmentioning
confidence: 98%
“…Various workers have reported that soil aggregates are stabilised by diverse mechanisms and perform differently against external factors, namely, rain, wind, irrigation and other farm management practices (Blanco‐Canqui & Lal, ; Bronick & Lal, ). These management practices in turn influence the relative distribution of aggregate mass, their stability (Cerdà, ; Saygin, Erpul, & Basaran, ; Yagüe, Domingo‐Olivé, Bosch‐Serra, Poch, & Boixadera, ; Mamedov, Huang, Aliev, & Levy, ) and the distribution of C and nitrogen (N) in these aggregates (Bandyopadhyay & Lal, ; Sundermeier, Islam, Raut, Reeder, & Dick, ). Of late, worldwide conservation agriculture (CA)/no‐till (NT) farming has gained impetus, and land under the CA regime has increased in area up to 124 m ha −1 by 2012 (Friedrich, Derpsch, & Kassam, ; Palm, Blanco‐Canqui, DeClerck, & Gatere, ), which was considered a sustainable and feasible approach to improve soil aggregation and also sustain or increase SOC (Powlson, Whitmore, & Goulding, ; Dalal, Allen, Wang, Reeves, & Gibson, ; Kahlon, Lal, & Varughese, : Palm et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent review of the literature found that quantification and interpretation of aggregate stability data were hampered by a lack of standardized procedures (Almajmaie, Hardie, Acuna, et al, ). Therefore, it is not surprising that modifications and new methods are being investigated (Efrat, Rawlins, Quinton, Watts, & Whitmore, ; Józefaciuk & Czachor, ; Rawlins, Turner, Wragg, Mc Lachlan, & Lark, ; Rawlins, Wragg, & Lark, ; Saygin, Erpul, & Basaran, ).…”
Section: Introductionmentioning
confidence: 99%